PENGARUH PENGALIHAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN TERHADAP BELANJA MODAL DENGAN PENDAPATAN ASLI DAERAH SEBAGAI VARIABEL PEMODERASI - Zikri, Unazir Achmad; Asmara, Jhon Andra (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
ABSTRACT This study aimed to examine the effect of the transition tax land and building in village and city towards capital expenditure with regional real revenue as the moderating variable. The data used in this research is secondary data. The sample was taken by purposive sampling method and the number of samples obtained were 17 district/city in the province of Aceh in 2014 and  2015. The analysis technique used is moderated regression analysis using SPSS 23.This  study  uses  tax  land  and  building  in  village  and  city  as  the  independent  variable  and  capital expenditure as the dependent variable, and then regional real revenue as the moderating variable. The results of this study indicate that the simultaneous testing (test F), tax land and building in village and city and regional real revenue has an effect on capital expenditure. In the partial test (t test), variable tax land and building in village and city and regional real revenue has no  effect on capital expenditure. Keywords: Tax land and building in village and city, capital expenditure, and regional real revenue